Oil and gas development influences big‐game hunting in Wyoming. Issue 3 (18th December 2016) - Dorning, Monica A.; Garman, Steven L.; Diffendorfer, Jay E.; Semmens, Darius J.; Hawbaker, Todd J.; Bagstad, Kenneth J.
ABSTRACT: Development from extracting oil and gas resources can have unintended effects on multiple ecosystem functions, with cascading effects on wildlife, ecosystem services, and local economies. Big‐game hunting opportunities may be closely related to these effects, but empirical analyses of impacts of energy development on hunting are limited. We examined the influence of oil and gas development density on harvest efficiency, or harvest per unit of hunter effort, within all hunt areas in Wyoming, USA, from 2008 to 2014 for 3 big‐game species: elk ( Cervus canadensis ), mule deer ( Odocoileus hemionus ), and pronghorn ( Antilocapra americana ). Using harvest/hunter day as the response variable, we compared linear mixed‐effects models for each species that included total well density (i.e., all wells constructed up to the year of record), active well density (i.e., only those wells currently producing oil or gas in that year), or neither as a predictor variable. We used well densities as indicators of development in the absence of data specifying the locations of other oil and gas infrastructure (e.g., roads, well pads). Models also accounted for the fixed effects of road density, hunter density, proportion of the area that is public land with unrestricted hunter access, proportion of the area that is forested, year of observation, and random effects of variation among hunt areas nested within associated game herd units. Presence of oil and gas wells had a positive influence on harvest efficiency for elk and mule deer. Although there was no overall effect to pronghorn, there was a negative influence of wells on juvenile pronghorn harvest efficiency. Changes in harvest efficiency due to expanding oil and gas development could alter the time spent hunting by hunters and their chances of harvesting an animal. This could have subsequent impacts on hunter satisfaction, game populations, and economic revenue generated from recreational hunters. © 2016 The Wildlife Society. Abstract : Our analyses provide evidence for changes in harvest efficiency of elk, mule deer, and pronghorn associated with oil and gas well densities, with effects depending on species and demographic group. Our results have implications for hunter satisfaction, wildlife management techniques, and local economies.